Effect of silane coupling agents on basalt fiber–epoxidized vegetable oil matrix composite materials analyzed by the single fiber fragmentation technique. Issue 7 (8th April 2014) - Samper, M.D.; Petrucci, R.; Sánchez‐Nacher, L.; Balart, R.; Kenny, J.M.
<x xml:space="preserve">Abstract</x> The fiber–matrix interfacial shear strength (IFSS) of biobased epoxy composites reinforced with basalt fiber was investigated by the fragmentation method. Basalt fibers were modified with four different silanes, (3‐aminopropyl)trimethoxysilane, [3‐(2‐aminoethylamino)propyl]‐trimethoxysilane, trimethoxy[2‐(7‐oxabicyclo[4.1.0]hept‐3‐yl)ethyl]silane and (3‐glycidyloxypropyl)trimethoxysilane to improve the adhesion between the basalt fiber and the resin. The analysis of the fiber tensile strength results was performed in terms of statistical parameters. The tensile strength of silane‐treated basalt fiber is higher than the tensile strength of the untreated basalt fiber; this behavior may be due to flaw healing effect on the defected fiber surfaces. The IFSS results on the composites confirm that the interaction between the fiber modified with coupling agents and the bio‐based epoxy resin was much stronger than that with the untreated basalt fiber. POLYM. COMPOS., 36:1205–1212, 2015. © 2014 Society of Plastics Engineers